Leading Risk Factors for Congenital Deafness in the Context of Universal Neonatal Screening: Our Observations in a Four-Year Retrospective Study - Antoine Paul; Fanny Bense; Claire Boithias Guerot; Sofia De La Rubia; Cécile Lebeaux; Jean-François Papon (MDPI AG, 2024)
It has been demonstrated that universal hearing neonatal screening (UHNS) is efficient at providing early diagnosis and rehabilitation for deafness. The risk factors of deafness in children have been identified, but less specifically in those diagnosed after UHNS. In this study, we aim to study these factors in infants who were referred after screening and to compare our experience to recent data. We studied infants referred to our department for diagnosis after screening between January 2018 and December 2021. Their medical history and neonatal hearing risk factors were assessed. Associations between factors were also analyzed. Sixty-six infants were included. A family history of deafness (47%), syndromic deafness (41%), intrauterine growth retardation or prematurity (19.7%), and prolonged NICU admission (18%) were the most observed factors. When analyzing according to these associations, family history of deafness and syndromic cases remained the most prevalent factors (74%), while only five cases (7.8%) presented with other neonatal risk factors only. The majority of congenital hearing loss cases are observed in infants with suspected genetic deafness. Parental counseling, the diagnostic pathway, as well as the healthcare system should be adapted according to these risk factors.